(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Human Papilloma virus (HPV) is the cause of a sexually transmitted infection which can lead to the development of genital warts, anogenital and oropharyngeal cancers. In Europe, about 90% of HPV-related cancers and 90% of genital warts are estimated to be vaccine preventable each year. In Italy, around 5,000 cases of cancers are due to HPV infections each year. This explains why HPV infection control is considered a public health priority.